The Effect of Cigarette Taxes on Cigarette Consumption Behavior in Indonesia - Amstrong Lambok Marihot Pangaribuan; Iqal Aulia Fawwas; Rohman Nelanda Syahputra; Renny Maisyarah (Universitas Muhammadiyah Palu, 2026)
Cigarette consumption in Indonesia remains relatively high despite the government’s implementation of cigarette excise tax policies as fiscal instruments and consumption control measures. This study aims to analyze the effect of cigarette excise taxes on smoking consumption behavior in Indonesia. The research employs a literature review method with a descriptive-analytical approach, utilizing secondary data from publications of the Ministry of Finance and scholarly journals that examine the relationship between cigarette prices, income levels, and consumption patterns. The findings indicate that increases in cigarette excise taxes, which lead to higher cigarette prices, tend to reduce consumption levels, particularly among low-income groups and light smokers. However, the impact is relatively smaller among higher-income groups. Therefore, cigarette excise taxes are shown to influence changes in smoking consumption behavior, although their effectiveness still requires supporting policies to ensure a more equitable and comprehensive impact.